A cross-national qualitative study on instructor perspectives for teaching internationally divers students. The teachers’ voices on faculty development - Fedeli, Monica; E. Coryell, Joellen; Frison, Daniela; Tyner, Jonathan (ITALIAN JOURNAL OF EDUCATIONAL RESEARCH, 2019)
This paper describes a component of a larger cross-national qualitative study on faculty development for teaching international students. Here we describe the study and report findings that offer analyses of the informal and formal means by which Italian and U.S. university instructors enhance the knowledge and skills they find necessary to teach international students successfully in this era of educational globalization. We also offer insights and challenges of conducting cross-national adult higher educational research and explain why such studies are essential in understanding how the world of academe is learning to adapt to globalization and international student mobility.